The meaning and importance of process safety competency - Baybutt, Paul (Process safety progress, 2016)
Process safety competency is subject to regulation in some jurisdictions, such as in the United Kingdom by the Health and Safety Executive (UK HSE) under the Control of Major Accident Hazard regulations. Process safety competency is one of 20 elements in the risk‐based process safety (RBPS) management system developed by the Center for Chemical Process Safety (CCPS). However, competency as used in this RBPS element is not the same as the competency regulated by the UK HSE. The RBPS competency element addresses managing a knowledge base of process information and not competency as defined by other CCPS publications which use the term with a similar meaning to the UK HSE. This makes for a confusing situation for companies interested in improving their management of process safety competency. The scope of the RBPS element should be revised to address true competency. Currently, the U.S. Occupational Safety and Health Administration's Process Safety Management Standard and the U.S. Environmental Protection Agency's Risk Management Program rule do not address competency. However, both regulators are considering revisions to these regulations, including the incorporation of additional elements from the CCPS RBPS management system that are not currently in the regulations. One of these elements is process safety competency, as defined in the CCPS RBPS management system. This action would result in an inadequate treatment of competency. If a competency element is incorporated into the regulations, it should address true competency. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 171–175, 2016